Structural, optical and elastic properties of zinc oxide soda lime silicate glass - Mohd Zaid, Mohd Hafiz (2011)
So far, most research had been done to understand the properties and advantages of soda lime silicate (SLS) glass compare to others glass and also to improve their quality. Addition of oxide into the glass system had been a topic of research for nearly half century, but many questions still remain unanswered concerning to the effect of the addition of some oxide to the properties and the structure changes of the glass. In this research, fabrication of a series of (ZnO)x(SLS)1-x glasses with weight percentage x from 0.05 to 0.40 were carried out by the melting and quenching technique. The chemical composition of the (ZnO)x(SLS)1-x glasses were determined using Inductive Couple Plasma (ICP) and Energy Dispersive X-ray Fluorescence (EDXRF). The amorphous structure of the glass samples were confirmed using X-ray diffraction (XRD) measurement. The glass density was measured by using Archimedes’ principle. The densities of the glass sample were increased with the addition of ZnO. The molar volume of the glass samples shows a same trend with the density of the glasses which is increased with the increased of ZnO content. Their physical properties such as elastic properties were determined at room temperature by using non-destructive test; the digital signal processing technique of Matec DSP MBS 8000. The experimental data of wave velocities and densities were then used to determine the longitudinal modulus, shear modulus, Young modulus, bulk modulus, Poisson’s ratio, fractal bond connectivity and Micro-hardness in each series of (ZnO)x(SLS)1-x glass system. It was found that the longitudinal modulus, shear modulus, Young modulus and bulk modulus decreased with the addition of ZnO in the SLS glasses. These elastic properties of glasses were found closely related to the strength of the glass structure. The values of the elastic properties had been compared with the Rocherulle’s model and this model shows a same trend which is the values of the longitudinal modulus, shear modulus, Young modulus and bulk modulus of the glass samples decreased with the addition of ZnO. The bonding in the (ZnO)x(SLS)1-x glasses were measured using IR Spectroscopy. The shift band of IR spectroscopy must be occurs due to the addition of ZnO, which means increase the non-bridging oxygens (NBOs) in the glass structure and resulting the structural of the glass samples become weaker. The optical properties of the (ZnO)x(SLS)1-x glass system were measured using UV-Visible spectroscopy. The values of the optical band gap decreased with the addition of ZnO in the SLS glass system